APPLICATION OF FISH SPECIES BALLONS FISH USING MACROMEDIA FLASH 5.0 - Muhammad Rohyat. P.; Hariyanto Hariyanto Skom, MMsi (Jurnal Sistem Informasi, 2004)
Multimedia is a new concept and technology in the field of information technology.Where text, images, sound, animation, and video incorporated into the computer to bestored, processed and presented on a linear or interactive.Birth of multimedia technology is the result of the advancement of electronictechnology, computers and software. So with this multimedia technology will changethe human task becomes easier.